Portrayal of Female Characters in Pakistani Private TV Dramas - Farhan Mushtaq,; Dr. Arshad Ali, (Journal of Peace, Development and Communication, 2022)
Over the decades, television transformed human life in different ways by providing society with a plenty of new interpretations; also, by strengthening and cultivating some old ones. Broadcasting of information and entertainment-based programs played a pivotal role in transforming Pakistani society as well. In the year 2002, the mushroom growth of private TV channels in Pakistan increased the demands of viewers for diverse content. The private networks along with heavy news production started entertainment telecasting majorly television dramas which is a “female-viewer-attracted” industry. The aim of this trend study is to critically observe how female characters are portrayed in the TV dramas of Pakistani private television channels from the year 2006 – 2016. Textual analysis is selected as method of analysis backed by theoretical framework of media representation theory in relation to feminism. It was found that there is a perspective of gender dichotomy in the TV dramas. Male lead character is active while female is passive in nature. Portrayal of women in drama re-assert patriarchal and sexist notions associated with behavior, occupation and appearance.